Pristine and magnetic kenaf fiber biochar for cd2+ adsorption from aqueous solution - Saeed, A. A. H. (MDPI, 2021)
Development of strategies for removing heavy metals from aquatic environments is in high demand. Cadmium is one of the most dangerous metals in the environment, even under extremely low quantities. In this study, kenaf and magnetic biochar composite were prepared for the adsorption of Cd2+. The synthesized biochar was characterized using (a vibrating-sample mag-netometer VSM), Scanning electron microscopy (SEM), X-ray powder diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS). The adsorp-tion batch study was carried out to investigate the influence of pH, kinetics, isotherm, and ther-modynamics on Cd2+ adsorption. The characterization results demonstrated that the biochar con-tained iron particles that help in improving the textural properties (i.e., surface area and pore volume), increasing the number of oxygen-containing groups, and forming inner-sphere com-plexes with oxygen-containing groups. The adsorption study results show that optimum adsorp-tion was achieved under pH 5–6. An increase in initial ion concentration and solution temperature resulted in increased adsorption capacity. Surface modification of biochar using iron oxide for imposing magnetic property allowed for easy separation by external magnet and regeneration. The magnetic biochar composite also showed a higher affinity to Cd2+ than the pristine biochar. The adsorption data fit well with the pseudo-second-order and the Langmuir isotherm, with the maximum adsorption capacity of 47.90 mg/g.